Gender and Investment Trends: The Role of Gender in Entrepreneur- Investor Relationship - Raees, Sakheela; Raheem, Zakir (Advances in Social Sciences Research Journal, 2017)
Behavioral Science is an emerging field which describes the emotional psychological pattern of individual investor during decision making process. The underneath study helps to examine the impact of gender on investment trends. For the purpose of collecting data, individual investors were chosen as respondents and a close ended questionnaire was used as an instrument of data collection. Investment trends were divided in six categories namely, stocks, commodities, gold, foreign exchange, bonds and real estate. The result exhibit that gender has sound impact in investment areas like Commodities and Real estate .Preferences of individual investors towards different types of investment choices made by each gender were also found. It was observed that majority of the male investors i.e. 52.5% preferred to make investment in real estate. Whereas 11.5%. Females were mostly inclined to make investment in gold. Results reveal female investors were found to show conservative behavior while male investors were aggressive when it comes to make investment.